Translanguaging - Garcia, O. author. aut Link
X, 165 p.
Keywords: Winner of the British Association of Applied Linguistics Book Prize 2015 This book addresses how the new linguistic concept of 'Translanguaging' has contributed to our understandings of language, bilingualism and education, with potential to transform not only semiotic systems and speaker subjectivities, but also social structures.